Iron phosphate dihydrate, preparation method thereof, iron phosphate and battery cathode material

CN122977334APending Publication Date: 2026-10-27GUIZHOU CNGR XINGYANG ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610999300.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0014]第四方面,本申请实施例提供一种电池正极材料,电池正极材料的原料包括本申请第二方面的实施例中的磷酸铁。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977334A_ABST
    Figure CN122977334A_ABST
Patent Text Reader

Abstract

The application provides ferriphosphate dihydrate, a preparation method thereof, ferriphosphate and a battery positive electrode material. The phase of the ferriphosphate dihydrate includes a monoclinic phase and an orthorhombic phase, wherein the proportion of the orthorhombic phase is 50% to 85%; and the particle size variation coefficient of the ferriphosphate dihydrate is less than 25%. The ferriphosphate dihydrate in the application is a mixed phase structure in which the monoclinic phase and the orthorhombic phase coexist. Through synergistic regulation of the phase ratio and the particle uniformity, the structural performance of the precursor and the electrochemical comprehensive performance of the subsequent battery positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of cathode material technology, specifically relating to a dihydrate iron phosphate and its preparation method, iron phosphate and battery cathode material. Background Technology

[0002] Lithium-ion batteries, with their outstanding advantages such as high energy density, long cycle life, and low self-discharge rate, are widely used in portable electronic devices, electric vehicles, and large-scale energy storage. With the rapid development of these applications, the performance requirements for lithium-ion batteries are also increasing, especially in high-power applications such as the rapid acceleration, hill climbing, and instantaneous high-power discharge of electric vehicles, which place stringent demands on the battery's high-power performance.

[0003] Lithium iron phosphate (LiFePO4) has become one of the mainstream cathode materials for power batteries and energy storage systems in new energy vehicles due to its low cost, environmental friendliness, excellent thermal stability, and high safety. As a key component of lithium-ion batteries, the performance of the cathode material largely determines the overall performance of the battery. Therefore, the development of high-performance cathode material precursors has become a research hotspot and key direction in the current lithium-ion battery field. Summary of the Invention

[0004] This application provides a method for preparing iron phosphate dihydrate, iron phosphate and battery cathode material, which has a higher orthogonal ratio and uniform and controllable particle size, which is beneficial to improving sintering consistency, thereby improving the batch stability and consistency of lithium iron phosphate.

[0005] In a first aspect, embodiments of this application provide ferric phosphate dihydrate, wherein the phases of ferric phosphate dihydrate include a monoclinic phase and an orthorhombic phase, wherein the orthorhombic phase accounts for 50% to 85%; and the particle size variation coefficient of ferric phosphate dihydrate is <25%.

[0006] According to the embodiments of the first aspect of this application, the particle size variation coefficient of ferric phosphate dihydrate is ≤20%.

[0007] According to an embodiment of the first aspect of this application, ferric phosphate dihydrate satisfies one or more of the following conditions: (1) ferric phosphate dihydrate comprises near-spherical particles with a sphericity of 0.8 to 1.0; (2) ferric phosphate dihydrate comprises near-spherical particles with an average particle size of 50 nm to 800 nm; (3) ferric phosphate dihydrate has a specific surface area of ​​3 m² / m³. 2 / g~30m 2 / g; (4) The tap density of ferric phosphate dihydrate is 0.4 g / cm³. 3 ~2g / cm 3 Optionally, the tap density of ferric phosphate dihydrate is 0.4 g / cm³. 3 ~1g / cm 3(5) The iron-to-phosphorus molar ratio of ferric phosphate dihydrate is 0.93~0.995; (6) The chemical formula of ferric phosphate dihydrate is Fe x M y PO4•2H2O; wherein, 0.95≤x≤1.00; 0≤y≤0.02; M includes one or more of Mn, V, Ti, Mg, Ca, Zn, Cu, Co, Ni, Al, Ga, In, La, Cr, and W.

[0008] Secondly, embodiments of this application provide a method for preparing ferric phosphate dihydrate, comprising: mixing a soluble iron salt solution, an ammonium phosphate solution and an oxidant to carry out a first coprecipitation reaction, aging to obtain an ferric phosphate intermediate; and mixing raw materials containing the ferric phosphate intermediate with a mixed acid solution to carry out a second coprecipitation reaction to obtain ferric phosphate dihydrate.

[0009] According to an embodiment of the second aspect of this application, the step of mixing the raw material containing the ferric phosphate intermediate with the mixed acid solution to carry out the second coprecipitation reaction is selected from one of the following methods: Method 1: Mix the acidic medium and the buffer medium to obtain a mixed acid solution; heat the mixed acid solution to a preset slurrying temperature I; add the ferric phosphate intermediate to the heated mixed acid solution for slurrying treatment I to obtain a slurry mixture; heat the slurry mixture to a preset aging temperature I for aging treatment to obtain ferric phosphate dihydrate. Method 2: Add pure water to the ferric phosphate intermediate to prepare a solution containing the ferric phosphate intermediate; mix the acidic medium and buffer medium to obtain a mixed acid solution; heat the solution containing the ferric phosphate intermediate to a preset slurrying temperature II; add the mixed acid solution to the heated solution containing the ferric phosphate intermediate for slurrying treatment II to obtain a slurry mixture; heat the slurry mixture to a preset aging temperature II for aging treatment to obtain ferric phosphate dihydrate.

[0010] According to an embodiment of the second aspect of this application, the preparation method satisfies at least one of the following conditions: A. The preset pulping temperature I and preset pulping temperature II are each independently 70~85℃; optionally, the preset pulping temperature I and preset pulping temperature II are each independently 75~85℃; B. The pulping treatment I and pulping treatment II each have a time of 30-80 min independently; C. The preset aging temperature I and preset aging temperature II are each independently set to 90~100℃; D. The aging treatment I and aging treatment II are each independently 90~150min; E. Acidic media include phosphoric acid and sulfuric acid.

[0011] According to an embodiment of the second aspect of this application, the preparation method satisfies at least one of the following conditions: (a) Soluble iron salts include ferrous salts, which may be one or more of ferrous sulfate, ferrous chloride, ferrous oxalate, ferrous phosphate, and ferrous hydrogen phosphate; (b) Oxidizing agents include one or more of hydrogen peroxide, ozone, oxygen, and air; (c) The buffer medium includes one or more of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, ammonium sulfate, and ammonia water; (d) The raw material also includes solution M, where M is one or more of manganese, vanadium, titanium, magnesium, calcium, zinc, copper, cobalt, nickel, aluminum, gallium, indium, lanthanum, chromium, and tungsten; optionally, the molar ratio of M to iron in ferric phosphate is 0 to 0.04. (e) The molar ratio of soluble iron salt solution, ammonium phosphate solution and oxidant, calculated as iron atoms and phosphorus atoms, is Fe:P:oxidant (0.95~1.20):1:(0.6~0.7). (f) The molar ratio of Fe:N:P:S in the reaction system formed by the iron phosphate intermediate and the mixed acid solution, based on iron atoms, nitrogen atoms, phosphorus atoms, and sulfur atoms, is 1:(0.32-0.52):(0.7-1.3):(0.32-0.58); optionally, the molar ratio of Fe:N:P:S in the reaction system formed by the iron phosphate intermediate and the mixed acid solution is 1:(0.32-0.52):(0.7-1.1):(0.32-0.58); (g) The ammonium phosphate solution is selected from any one or more of the following: ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.

[0012] Thirdly, embodiments of this application provide an iron phosphate, which is obtained by heat treatment of iron phosphate dihydrate prepared by the preparation method in the first aspect of this application or the second aspect of this application.

[0013] According to an embodiment of the third aspect of this application, ferric phosphate satisfies at least one of the following conditions: (i) the specific surface area of ​​ferric phosphate is 8 m². 2 / g~20m 2 / g; (ii) the iron-to-phosphorus molar ratio of ferric phosphate is 0.985~0.995; (iii) the particle size variation coefficient of ferric phosphate is less than <25%; (iv) the tap density of ferric phosphate is 0.6 g / cm³. 3 -0.8 g / cm 3 .

[0014] Fourthly, embodiments of this application provide a battery positive electrode material, the raw materials of which include iron phosphate as described in the embodiments of the second aspect of this application.

[0015] The particle size variation coefficient of iron phosphate dihydrate in this embodiment is <25%, and the particle size is uniform and controllable, which is beneficial to improving sintering consistency and thus improving the batch stability and consistency of lithium iron phosphate. Furthermore, it is an orthogonal and monoclinic mixed phase, with the orthogonal phase accounting for more than the monoclinic phase. The orthogonal phase is a thermodynamically stable phase, and its proportion of more than half makes the iron phosphate dihydrate structure more regular and the crystallinity higher, resulting in good batch stability. This leads to a long cycle life and good thermal stability of the battery cathode material. The presence of a portion of monoclinic phase will form defect sites and ion channels during the sintering process, resulting in a more complete lithiation reaction and good rate performance of the battery cathode material. Attached Figure Description

[0016] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0017] Figure 1 The SEM image of ferric phosphate dihydrate of Example 1 of this application is shown; Figure 2 The SEM image of ferric phosphate of Example 1 of this application is shown; Figure 3 The SEM image of ferric phosphate dihydrate of Comparative Example 1 of this application is shown; Figure 4 The SEM image of iron phosphate in Comparative Example 1 of this application is shown. Detailed Implementation

[0018] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the present application, including iron phosphate dihydrate, its preparation method, iron phosphate, and battery cathode materials. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of essentially identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand the present application and are not intended to limit the subject matter of the claims.

[0019] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is understood that ranges of 60~110 and 80~120 are also expected. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, characterized in that a and b are both real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0020] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0021] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.

[0022] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0023] In this application, "multiple" refers to two or more (including two). In this application, "multiple times" refers to two or more (including two).

[0024] In this application, the particle size variation coefficient characterizes the dispersion and uniformity of particle size, and is the ratio of the standard deviation of particle size to the average size. The size of N (N≥50) particles is measured using a Nanomeasurer, and the standard deviation and average size of the N particle sizes are calculated to obtain the particle size variation coefficient. The size of a single particle is measured by selecting the maximum distance between two points on the outer contour edge of the particle.

[0025] In this application, quasi-spherical is used to describe the shape of particles; quasi-spherical is a general term for elliptical or circular bodies of revolution.

[0026] In this application, the sphericity is calculated as follows: all particles in the SEM image are identified using electron microscopy recognition software, and the sphericity is calculated using the formula: sphericity = area of ​​the circumcircle corresponding to the shortest diameter / area of ​​the circumcircle corresponding to the longest diameter × 100%.

[0027] In this application, particle size Dv50 and average particle size have the same meaning, referring to the particle size corresponding to the cumulative particle size distribution percentage of ferric phosphate dihydrate reaching 50%.

[0028] In view of the need to improve the performance of batteries in the prior art, this application provides iron phosphate dihydrate, its preparation method, iron phosphate, and battery cathode material.

[0029] In a first aspect, embodiments of this application provide ferric phosphate dihydrate, wherein the phases of ferric phosphate dihydrate include a monoclinic phase and an orthorhombic phase, wherein the orthorhombic phase accounts for 50% to 85%; and the particle size variation coefficient of ferric phosphate dihydrate is <25%.

[0030] The iron phosphate dihydrate in this embodiment is a mixed-phase structure in which monoclinic and orthorhombic phases coexist, with the orthorhombic phase accounting for 50% to 85% and the particle size variation coefficient being less than 25%. Through the synergistic regulation of phase ratio and particle uniformity, the structural performance of the precursor and the electrochemical comprehensive performance of the subsequent battery cathode material are improved.

[0031] Specifically, the particle size variation coefficient is controlled within 25%, ensuring uniform particle size of iron phosphate dihydrate and reducing the problems of uneven particle size and local agglomeration in traditional precursors. Uniform particles facilitate consistent heating, mass transfer, and crystallization rates during subsequent high-temperature sintering, improving sintering stability and batch stability and consistency of lithium iron phosphate products.

[0032] Meanwhile, this application uses a thermodynamically more stable orthorhombic phase as the main phase, with the orthorhombic phase accounting for a higher proportion than the monoclinic phase. After the proportion exceeds half, the iron phosphate dihydrate structure becomes more regular, the crystallinity is higher, and the batch stability is better, resulting in a longer cycle life and better thermal stability of the battery cathode material.

[0033] In addition, retaining an appropriate proportion of monoclinic phase as an auxiliary phase in the system can introduce appropriate defect sites and ion channels during the subsequent sintering process, making the lithiation reaction more complete, the rate performance of the battery cathode material better, and the overall electrochemical performance more balanced.

[0034] For example, the orthogonal phase ratio can be any value or a range between any two of 50%, 52%, 54%, 55%, 56%, 58%, 60%, 62%, 64%, 65%, 66%, 68%, 70%, 72%, 74%, 75%, 76%, 78%, 80%, 82%, 84%, and 85%.

[0035] For example, the particle size variation coefficient can be any value less than 25% or any value between 24%, 23%, 22%, 20%, 19%, 18%, 15%, 10%, and 5%, or any value between both.

[0036] In some embodiments, the particle size variation coefficient of ferric phosphate dihydrate is ≤20%.

[0037] In the embodiments of this application, the particle size variation coefficient of ferric phosphate dihydrate is ≤20%, which makes the particle size and morphology of the precursor highly uniform. This can improve the shortcomings of traditional ferric phosphate dihydrate, such as the differentiation of coarse and fine particles and the mixing of fine powder and large particles, and reduce the difference between excessive sintering of fine powder and incomplete sintering of coarse powder during the sintering process.

[0038] The highly uniform particle system ensures that the heating efficiency, crystallization growth rate, and element diffusion of the particles remain largely synchronized during batch sintering, improving sintering consistency and controllability, further reducing batch-to-batch variations, and enhancing the batch stability of lithium iron phosphate products. Simultaneously, the uniform particle structure enables the formation of a regular and stable precursor stacking structure, allowing subsequent lithium sources and doping elements to be uniformly adsorbed and permeated onto the particle surface. This ensures that the lithiation and doping modification reactions proceed uniformly and fully, effectively improving the lattice integrity and structural uniformity of the lithium iron phosphate material, resulting in superior overall electrochemical performance.

[0039] In some embodiments, the chemical formula of ferric phosphate dihydrate is Fe. x M y PO4•2H2O; wherein, 0.95≤x≤1.00; 0≤y≤0.02; M includes one or more of Mn, V, Ti, Mg, Ca, Zn, Cu, Co, Ni, Al, Ga, In, La, Cr, and W.

[0040] The ferric phosphate dihydrate in the embodiments of this application can be represented by the above general chemical formula.

[0041] For example, x can take any value from 0.95, 0.96, 0.97, 0.98, 0.99, and 1.00, or a range between any two.

[0042] For example, y can take any value from 0, 0.005, 0.01, 0.015 and 0.02 or a range between any two.

[0043] In some embodiments, ferric phosphate dihydrate comprises near-spherical particles with a sphericity of 0.8 to 1.0.

[0044] Ferric phosphate dihydrate particles exhibit a near-spherical morphology, with particle sphericity controlled within the range of 0.8 to 1.0. High sphericity particles are more densely packed, which is beneficial for improving compaction; furthermore, the structure possesses superior powder packing properties and flowability, reducing frictional resistance between powder particles, minimizing powder agglomeration, and enhancing the uniformity of materials during batching, mixing, and sintering processes.

[0045] For example, the sphericity of the particles is any value among 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, and 1.0, or a range between any two.

[0046] In some embodiments, ferric phosphate dihydrate comprises near-spherical particles with an average particle size of 50 nm to 800 nm.

[0047] In some embodiments, the specific surface area of ​​ferric phosphate dihydrate is 3 m². 2 / g~30m 2 / g.

[0048] In this embodiment, the average particle size of iron phosphate dihydrate is controlled to be 50nm~800nm. The small particle size and short ion transport path can shorten the migration distance of lithium ions in the subsequent lithiation reaction, improve the lithiation reaction rate and reaction sufficiency, and optimize the rate charge and discharge performance of lithium iron phosphate material.

[0049] The specific surface area of ​​ferric phosphate dihydrate was controlled at 3 m². 2 / g~30m 2 Within the / g range, a suitable specific surface area can provide sufficient active reaction sites for lithium source adsorption, doping modification, and solid-state sintering reactions, effectively improving the electrochemical activity of the material.

[0050] For example, the average particle size of ferric phosphate dihydrate is any value or a range between 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm and 800 nm.

[0051] For example, the specific surface area of ​​ferric phosphate dihydrate is 3 m². 2 / g、5m 2 / g、7m 2 / g、9m 2 / g, 10m 2 / g、12m 2 / g、14m 2 / g, 15m 2 / g, 16m 2 / g、18m 2 / g、20m 2 / g、22m 2 / g、23m 2 / g、25m 2 / g、26m 2 / g、28m 2 / g, and 30m 2 Any value in / g or any range between the two.

[0052] In some embodiments, the tap density of ferric phosphate dihydrate is 0.4 g / cm³. 3 ~2g / cm 3 .

[0053] In the embodiments of this application, the tap density of ferric phosphate dihydrate within the above-mentioned range can improve the flowability of the material, enhance the flowability during sintering and packaging, and improve processing performance.

[0054] For example, the tap density of ferric phosphate dihydrate is 0.4 g / cm³. 3 0.5g / cm 3 0.6g / cm 3 0.7g / cm 3 0.8g / cm 3 1.0g / cm 3 1.2g / cm 3 1.4g / cm 3 1.5g / cm 3 1.6g / cm 3 1.8g / cm 3 and 2g / cm 3 Any value in the range or any value between the two.

[0055] In some embodiments, the iron-to-phosphorus molar ratio of ferric phosphate dihydrate is 0.93 to 0.995.

[0056] For example, the iron-to-phosphorus molar ratio of ferric phosphate dihydrate is any value or a range between any two of 0.93, 0.935, 0.94, 0.945, 0.95, 0.955, 0.96, 0.965, 0.97, 0.975, 0.98, 0.985, 0.99, and 0.995.

[0057] Secondly, this application provides a method for preparing ferric phosphate dihydrate, which adopts a co-precipitation reaction process. The overall process is simple, the conditions are easy to control, and it is suitable for industrial mass production.

[0058] The method for preparing ferric phosphate dihydrate provided in this application includes: mixing a soluble iron salt solution, an ammonium phosphate solution and an oxidant to carry out a first coprecipitation reaction, and aging to obtain an ferric phosphate intermediate; mixing the raw material containing the ferric phosphate intermediate with a mixed acid solution to carry out a second coprecipitation reaction to obtain ferric phosphate dihydrate.

[0059] Specifically, in the step of preparing the ferric phosphate intermediate, a soluble iron salt is prepared into a homogeneous soluble iron salt solution, while an ammonium phosphate solution and an oxidant are prepared. These three materials are then thoroughly mixed, and a first co-precipitation reaction occurs within the system. After the reaction is complete, the system is aged to obtain the ferric phosphate intermediate.

[0060] The soluble iron salt serves as the iron source for the system; ammonium phosphate, a water-soluble phosphate, simultaneously provides the required phosphorus and ammonium ions, acting not only as the phosphorus source but also as a buffer to pre-regulate the reaction environment; the oxidant participates in the reaction, promoting the solid-phase precipitation of iron phosphate. The iron phosphate intermediate obtained after co-precipitation and aging exhibits high reactivity and can be used as a raw material for subsequent reactions.

[0061] In some embodiments, the soluble iron salt includes a ferrous salt, which may be one or more of ferrous sulfate, ferrous chloride, ferrous oxalate, ferrous phosphate, and ferrous hydrogen phosphate. Ferrous salts have good solubility, are widely available, and have low impurity content, providing a stable iron source in the system.

[0062] In some embodiments, the ammonium phosphate solution is selected from any one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate in a mixed solution.

[0063] In some embodiments, the oxidant includes one or more of hydrogen peroxide, ozone, oxygen, and air.

[0064] The dosage of the above-mentioned oxidant is adjusted according to its oxidizing capacity to ensure that the ferrous ions in the system are fully oxidized to ferric ions, which is conducive to the smooth precipitation of high-purity iron phosphate. After the reaction, it decomposes into water without residual impurities, and the post-processing is easy.

[0065] In some embodiments, the molar ratio of soluble iron salt solution, ammonium phosphate solution and oxidant, based on iron atoms and phosphorus atoms, is Fe:P:oxidant (0.95~1.20):1:(0.6~0.7).

[0066] For the material ratio of the first coprecipitation reaction, based on iron and phosphorus atoms, the molar ratio of soluble iron salt solution, ammonium phosphate solution, and oxidant satisfies Fe:P:oxidant = (0.95~1.20):1:(0.6~0.7). This ratio range ensures a balanced ratio of iron and phosphorus sources, and the combination with the oxidant facilitates the complete oxidation of ferrous ions. This not only promotes the full progress of the precipitation reaction but also avoids material waste and impurity residue caused by excessive raw materials.

[0067] For example, based on iron atoms and phosphorus atoms, the molar ratio of soluble iron salt solution, ammonium phosphate solution and oxidant satisfies Fe:P:oxidant as (0.95~1.10):1:(0.6~0.7), (0.95~1.00):1:(0.6~0.7), (1.0~1.20):1:(0.6~0.7), (1.0~1.10):1:(0.6~0.7), (1.10~1.20):1:(0.6~0.7) or (0.95~1.20):1:(0.6~0.65).

[0068] In the preparation of ferric phosphate dihydrate, the ferric phosphate intermediate obtained above is mixed evenly with a mixed acid solution to carry out a second coprecipitation reaction. After the reaction is completed, conventional post-processing is performed to obtain the ferric phosphate dihydrate of the present application.

[0069] The mixed acid solution and the ferric phosphate intermediate work synergistically to complete crystal growth, phase construction and morphology control through a second coprecipitation reaction, ultimately yielding a finished product of ferric phosphate dihydrate with a specific phase composition and uniform particle size.

[0070] In some embodiments, the step of mixing the raw materials containing the ferric phosphate intermediate and the mixed acid solution for a second coprecipitation reaction can be carried out by the following method: mixing an acidic medium and a buffer medium to obtain a mixed acid solution; heating the mixed acid solution to a preset slurrying temperature I; adding the ferric phosphate intermediate to the heated mixed acid solution for slurrying treatment I to obtain a slurry mixture; heating the slurry mixture to a preset aging temperature I for aging treatment to obtain ferric phosphate dihydrate.

[0071] First, the acidic medium and buffer medium are mixed and stirred. This pre-mixing method allows the acidic components, buffer components and modifying agents to be fully mixed, avoiding uneven local material concentrations and creating a stable and uniform reaction environment for the subsequent crystallization reaction.

[0072] The prepared mixed acid solution is then heated to the preset slurrying temperature I, and then ferric phosphate intermediate is added to the heated mixed acid solution to obtain a slurry mixture. The isothermal slurrying stage allows the ferric phosphate intermediate to be fully immersed in the mixed system. With the activation effect of the acidic medium, the surface structure of the intermediate is opened, which is conducive to the full diffusion and contact of various ions in the system, realizing the fusion of materials and reaction medium, and completing the initial ion exchange and reaction.

[0073] After the pulping process is completed, the resulting pulp mixture is heated to the preset aging temperature I and subjected to isothermal aging treatment. Under the aging temperature conditions, recrystallization, grain growth, and phase transformation processes continuously occur within the system. The amorphous ferric phosphate intermediate gradually transforms into crystalline ferric phosphate dihydrate, while the grain morphology, particle size, and phase ratio gradually stabilize. The aging process can improve the crystal structure, reduce crystal defects, and ultimately form a ferric phosphate dihydrate product with the target morphology, particle size, and phase composition.

[0074] In some embodiments, the step of mixing the raw materials containing the ferric phosphate intermediate and the mixed acid solution for the second coprecipitation reaction can also be carried out by the following method: adding pure water to the ferric phosphate intermediate to prepare a solution containing the ferric phosphate intermediate; mixing the acidic medium and the buffer medium to obtain a mixed acid solution; heating the solution containing the ferric phosphate intermediate to a preset slurrying temperature II; adding the mixed acid solution to the heated solution containing the ferric phosphate intermediate for slurrying treatment II to obtain a slurryed mixture; heating the slurryed mixture to a preset aging temperature II for aging treatment to obtain ferric phosphate dihydrate.

[0075] In some embodiments, the acidic medium includes phosphoric acid and sulfuric acid.

[0076] The acidic medium used in the second coprecipitation reaction is phosphoric acid and sulfuric acid, which work together to create a stable acidic environment. This environment can activate the iron phosphate intermediate, regulate the acidity of the system to suit the crystal growth conditions, and guide the normal nucleation and growth of the crystals.

[0077] In some embodiments, the buffer medium includes one or more of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, ammonium sulfate, and ammonia water.

[0078] The aforementioned buffer medium can act as a pH buffer, suppressing drastic fluctuations in the acidity and alkalinity of the reaction system. At the same time, it can participate in the crystallization process as a reaction component, stabilizing the crystallization environment and avoiding problems such as abnormal grain morphology and widened grain size distribution caused by sudden changes in the system state.

[0079] In some embodiments, the raw material further includes solution M, where M is one or more of manganese, vanadium, titanium, magnesium, calcium, zinc, copper, cobalt, nickel, aluminum, gallium, indium, lanthanum, chromium, and tungsten; optionally, the molar ratio of M to iron in ferric phosphate is 0 to 0.04.

[0080] During the second coprecipitation and recrystallization process, the dopant elements can uniformly enter the crystal lattice or adhere to the particle surface to achieve the modification effect. Controlling the molar ratio of M to iron in ferric phosphate to 0~0.04 is beneficial to fully utilize the doping effect to optimize the crystal structure, and can also reduce the problems of lattice distortion and phase purity reduction caused by excessive doping, which is conducive to the overall stability of ferric phosphate dihydrate.

[0081] For example, the molar ratio of M to iron in ferric phosphate is any value among 0, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035 and 0.04 or any range between two.

[0082] A molar ratio of 0 between the metal element in the M source and the iron element in the iron phosphate indicates that M is not doped.

[0083] In some embodiments, the molar ratio of Fe:N:P:S in the reaction system formed by the ferric phosphate intermediate and the mixed acid solution, based on iron atoms, nitrogen atoms, phosphorus atoms, and sulfur atoms, is 1:(0.32-0.52):(0.7-1.3):(0.32-0.58); optionally, the molar ratio of Fe:N:P:S in the reaction system formed by the ferric phosphate intermediate and the mixed acid solution is 1:(0.32-0.52):(0.7-1.1):(0.32-0.58).

[0084] By adjusting the ratio of iron, nitrogen, phosphorus, and sulfur elements in the second coprecipitation reaction system, the acidic components, buffer components, and intermediates can fully interact, stabilize the crystallization environment, guide grain growth, phase transformation, and morphology control, and finally obtain a dihydrate iron phosphate product that meets the requirements in terms of phase ratio, particle size, sphericity, and other indicators.

[0085] For example, based on iron atoms, nitrogen atoms, phosphorus atoms, and sulfur atoms, the molar ratio of Fe:N:P:S in the reaction system formed by the iron phosphate intermediate and the mixed acid solution is 1:(0.32-0.52):(0.7-1.3):(0.32-0.58), 1:(0.35-0.52):(0.7-1.3):(0.32-0.58), 1:(0.35-0.45):(0.7-1.3):(0.32-0.58), 1:(0.40-0.50):(0.7-1.3):(0.32-0.58), 1:(0.32- 0.52):(0.8-1.3):(0.32-0.58), 1:(0.32-0.52):(0.9-1.3):(0.32-0.58), 1:(0.32-0.52):(0.9-1.2):(0.32-0.58), 1:(0.32-0.52):(0.7-1.3):(0.35-0.55), 1:(0.32-0.52):(0.7-1.3):(0.35-0.45) or 1:(0.35-0.45):(0.9-1.2):(0.35-0.45).

[0086] In some embodiments, the preparation method satisfies the following: the preset pulping temperature I and the preset pulping temperature II are each independently 70~85°C; optionally, the preset pulping temperature I and the preset pulping temperature II are each independently 75~85°C.

[0087] The above temperature range is conducive to the full activation of the iron phosphate intermediate by the acidic medium, accelerating the ion diffusion and material wetting rate. At the same time, it avoids insufficient activation and slow reaction rate due to excessively low temperature, and can also reduce the violent reaction of components in the system caused by excessively high temperature, which can lead to premature abnormal nucleation of crystals and deterioration of particle morphology.

[0088] For example, the preset pulping temperature I is any value among 70°C, 72°C, 75°C, 78°C, 80°C, 82°C and 85°C or a range between any two.

[0089] For example, the preset pulping temperature II is any value among 70°C, 72°C, 75°C, 78°C, 80°C, 82°C and 85°C or a range between any two.

[0090] In some embodiments, the preparation method satisfies the following: the time for pulping treatment I and pulping treatment II is 30~80 min each independently.

[0091] Sufficient pulping time is beneficial for the complete dispersion and uniform activation of ferric phosphate intermediates; if the time is insufficient, uneven material mixing and large differences in local activation levels may occur; if the time is too long, production efficiency will be reduced.

[0092] For example, the pulping treatment time I is any value among 30 min, 40 min, 50 min, 60 min, 70 min and 80 min or a range between any two.

[0093] For example, the pulping treatment II time is any value among 30 min, 40 min, 50 min, 60 min, 70 min and 80 min or a range between any two.

[0094] In some embodiments, the preparation method satisfies the following: the preset aging temperature I and the preset aging temperature II are each independently 90~100°C.

[0095] The aging stage is a critical stage for grain growth and phase stabilization. The above-mentioned temperature range can provide suitable crystallization driving force, which promotes the gradual transformation of amorphous intermediates into a mixed-phase structure in which monoclinic and orthorhombic phases coexist, thereby promoting regular grain growth and perfecting the crystal structure.

[0096] For example, the preset aging temperature I is any value among 90℃, 92℃, 94℃, 96℃, 98℃, and 100℃, or a range between any two.

[0097] For example, the preset aging temperature II is any value among 90°C, 92°C, 94°C, 96°C, 98°C, and 100°C, or a range between any two.

[0098] In some embodiments, the preparation method satisfies the following: the aging treatment I and aging treatment II are each independently 90~150 min.

[0099] The aging process allows the initial precipitate formed in the first stage to mature slowly, resulting in a more uniform ion distribution within the system, preliminary optimization of particle state, and improved overall uniformity of ferric phosphate. This time range allows the precipitate particle structure to stabilize, reducing the proportion of small, loose particles, while preventing particle agglomeration due to excessive aging time.

[0100] For example, the aging treatment I time is any value among 90 min, 100 min, 110 min, 120 min, 130 min, 140 min and 150 min or a range between any two.

[0101] For example, the aging treatment II time is any value or a range between 90 min, 100 min, 110 min, 120 min, 130 min, 140 min and 150 min.

[0102] Thirdly, embodiments of this application provide an iron phosphate, which is obtained by heat treatment of iron phosphate dihydrate prepared by the preparation method in the first aspect of this application or the second aspect of this application.

[0103] This application heat-treats the ferric phosphate dihydrate prepared by the preparation method in the first aspect of this application or the second aspect of this application to remove the water of crystallization from the ferric phosphate dihydrate, complete the lattice reorganization and crystal phase stabilization, and finally obtain ferric phosphate material with uniform particle size and excellent purity.

[0104] During heat treatment, the uniform particle morphology and reasonable mixed-phase structure of ferric phosphate dihydrate ensure simultaneous dehydration and crystallization of the entire material, effectively suppressing abnormal local grain growth, lattice distortion, and secondary agglomeration, thus maintaining uniform particle size and stable crystal structure in the resulting ferric phosphate. Simultaneously, the precisely controllable iron-phosphorus ratio, low coefficient of variation in particle size distribution, and high sphericity packing advantages of the precursor can be inherited by the finished ferric phosphate, giving it excellent powder flowability, packing density, and processing adaptability.

[0105] In some embodiments, the specific surface area of ​​iron phosphate is 8 m². 2 / g~20m 2 / g.

[0106] In some embodiments, the iron-to-phosphorus molar ratio of ferric phosphate is 0.985 to 0.995.

[0107] In some embodiments, the particle size variation coefficient of iron phosphate is less than 25%.

[0108] In some embodiments, the tap density of ferric phosphate is 0.6 g / cm³. 3 -0.8g / cm 3 .

[0109] Fourthly, embodiments of this application provide a battery positive electrode material, the raw materials of which include iron phosphate as described in the embodiments of the second aspect of this application.

[0110] In this application embodiment, the aforementioned iron phosphate is used as a precursor to prepare battery cathode material. Relying on the regular crystal structure and uniform particle size of iron phosphate, it provides high-quality raw materials for the preparation of battery cathode material, which is beneficial to improving the capacity, first efficiency and rate charge and discharge performance of the material.

[0111] Fifthly, embodiments of this application provide a secondary battery, including the battery positive electrode material described in the embodiments of the fourth aspect of this application.

[0112] The secondary battery provided in this application includes the above-mentioned battery positive electrode material.

[0113] Sixthly, this application provides an electrical device, including the secondary battery described in the fifth aspect of this application.

[0114] Example The following examples describe the disclosure of this invention in more detail. These examples are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of this disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized by conventional methods and can be used directly without further processing. The instruments used in the examples are also commercially available.

[0115] Example 1 This embodiment provides ferric phosphate dihydrate and ferric phosphate prepared therefrom, and the specific preparation steps are as follows: 1) Prepare ferrous sulfate solution, ammonium dihydrogen phosphate and ammonium monohydrogen phosphate solution respectively. Use hydrogen peroxide as oxidant. According to the molar ratio of Fe:P:oxidant of 1:1:0.65, thoroughly mix ferrous sulfate solution, ammonium phosphate solution and hydrogen peroxide to carry out the first coprecipitation reaction. The reaction temperature is controlled at 40-70℃. After the reaction is completed, age for 50 min. After solid-liquid separation, filtration and washing, ferric phosphate intermediate is obtained.

[0116] 2) Ammonia, phosphoric acid, and sulfuric acid were mixed to prepare a homogeneous acid solution. The solution was heated to a preset slurrying temperature of 175°C. Ferric phosphate intermediate was then added to the acid solution and kept at the preset slurrying temperature for 60 minutes. The reaction system of the ferric phosphate intermediate and the acid solution satisfied the molar ratio of Fe:N:P:S of 1:0.36:0.8:0.32. After slurrying, the temperature was raised to a preset aging temperature of 94°C after 30 minutes and held at this temperature for 120 minutes to complete the second co-precipitation reaction. After the reaction, the solution was filtered, washed, and dried to obtain ferric phosphate dihydrate. The SEM morphology of ferric phosphate dihydrate in this example is shown below. Figure 1 As shown in Table 1, the various physicochemical properties are as follows.

[0117] 3) The obtained ferric phosphate dihydrate was heat-treated at 620℃ for 4 hours, then pulverized and ground to obtain anhydrous ferric phosphate. The SEM morphology of the anhydrous ferric phosphate in this embodiment is as follows: Figure 2 As shown in Table 2, the various physicochemical properties are as follows.

[0118] Example 2 This embodiment provides ferric phosphate dihydrate and ferric phosphate prepared therefrom. The preparation method of this embodiment is basically similar to that of Example 1, except that the preset slurry temperature is adjusted to 85°C in the second coprecipitation process.

[0119] Example 3 This embodiment provides ferric phosphate dihydrate and ferric phosphate prepared therefrom. The preparation method of this embodiment is basically similar to that of Example 1, except that: (1) Titanium oxysulfate is added for titanium doping in the first coprecipitation reaction stage, that is, according to the molar ratio of Fe:P:oxidant:Ti of 1:1:0.65:0.005, ferrous sulfate solution, ammonium phosphate solution, hydrogen peroxide and titanium oxysulfate are fully mixed to carry out the first coprecipitation reaction. (2) In the second coprecipitation process, the preset slurry temperature is adjusted to 80℃.

[0120] Example 4 This embodiment provides ferric phosphate dihydrate and ferric phosphate prepared therefrom. The preparation method in this embodiment is basically similar to that in Example 1, except that: In the second coprecipitation process, the ferric phosphate intermediate is first added to pure water and dispersed at 75°C for 60 minutes to form a solution containing the ferric phosphate intermediate. Then, ammonia, phosphoric acid, and sulfuric acid are mixed to prepare a homogeneous mixed acid solution. The mixed acid solution is then added to the solution containing the ferric phosphate intermediate and kept at the preset slurry temperature of 75°C for 60 minutes. The reaction system of the ferric phosphate intermediate and the mixed acid solution satisfies the molar ratio of Fe:N:P:S of 1:0.4:1.3:0.4. After slurrying, the temperature is raised to the preset aging temperature of 94°C for 20 minutes and kept at a constant temperature for 90 minutes to complete the second coprecipitation reaction.

[0121] The physicochemical properties of the ferric phosphate dihydrate prepared in this embodiment are shown in Table 1; the ferric phosphate obtained after the same heat treatment contains a small amount of impurity phase, and its properties are shown in Table 2.

[0122] Example 5 This embodiment provides ferric phosphate dihydrate and ferric phosphate prepared therefrom. The preparation method in this embodiment is basically similar to that in Example 1, except that: In the second coprecipitation process, the reaction system of the ferric phosphate intermediate and the mixed acid solution satisfies the molar ratio of Fe:N:P:S as 1:0.36:1.2:0.32.

[0123] Comparative Example 1 This comparative example provides ferric phosphate dihydrate and ferric phosphate prepared therefrom. The preparation method of this comparative example is basically similar to that of Example 1, except that: In the second coprecipitation process, ammonia, phosphoric acid, and sulfuric acid are mixed to prepare a uniform mixed acid solution, and the mixed acid solution is heated to the preset slurry temperature of 85°C. The reaction system of ferric phosphate intermediate and mixed acid solution satisfies the molar ratio of Fe:N:P:S of 1:0.3:0.8:0.3.

[0124] The SEM morphology of the iron phosphate dihydrate prepared in this comparative example is as follows: Figure 3As shown in Table 1, the various physicochemical properties are shown in the table; the SEM morphology of the obtained iron phosphate is shown in the figure. Figure 4 As shown in Table 2, the performance parameters are as follows.

[0125] Comparative Example 2 This comparative example provides ferric phosphate dihydrate and ferric phosphate prepared therefrom. The preparation method of this comparative example is basically similar to that of Example 1, except that the preset slurry temperature is adjusted to 65°C in the second co-precipitation process.

[0126] Comparative Example 3 This comparative example provides ferric phosphate dihydrate and ferric phosphate prepared therefrom. The preparation method of this comparative example is basically similar to that of Example 1, except that the preset slurry temperature is adjusted to 90°C in the second co-precipitation process.

[0127] Test section The iron phosphate dihydrate and iron phosphate prepared in the examples and comparative examples were subjected to index parameter testing and electrochemical performance testing.

[0128] Tap density test method: The tap density is determined by a powder tap density tester, referring to the national standard GB / T5162-2021 "Determination of tap density of metal powder"; Specific surface area test method: The specific surface area was determined by a fully automated nitrogen adsorption specific surface area analyzer, referring to the national standard GB / T19587-2017 "Determination of specific surface area of ​​solid substances by gas adsorption BET method". Compacted density test method: The compacted density tester of Sansi Zongheng UIM 7305 was used. The test method is as follows: Weigh 1g of the material to be tested and place it in a clean mold. The radius of the hole in the mold is 13mm. Then place the mold on the pressure plate of the equipment and select the test pressure of 3T for testing. The iron phosphate from the examples and comparative examples was used to prepare lithium iron phosphate, and the specific operations are as follows: 1) Mix lithium carbonate, iron phosphate, titanium dioxide, glucose, and PEG in a Li / P molar ratio of 1.005, and add deionized water to prepare a slurry with a solid content of 38%.

[0129] 2) After mixing and stirring for 30 minutes, grind the slurry in a sand mill, and control the grinding D50 at 0.36~0.38μm.

[0130] 3) The slurry with qualified particle size after grinding is then introduced into a spray dryer by a peristaltic pump for drying and molding.

[0131] 4) Transfer the dried powder to a box furnace and sinter it under a nitrogen atmosphere. Control the heating rate to 2℃ / min, maintain it at 780℃ for 8 hours, and then let it cool naturally to room temperature to obtain the lithium iron phosphate cathode material.

[0132] The above-mentioned LFP / C cathode materials were prepared into cathode slurry with conductive carbon black, binder polyvinylidene fluoride, and solvent N-methylpyrrolidone. The cathode slurry was coated onto aluminum foil, then baked and dried, followed by vacuum drying, and finally die-cut to form LFP / C cathode sheets. Using LFP / C as the cathode, lithium sheet as the anode, and 1 mol / L LiPF6 EC / DMC / EMC solution as the electrolyte, a button cell was assembled. The electrochemical performance was tested using the Blue Electric CT3002A testing system. Charge-discharge tests at 0.1C and 1C (160 mA / g) were performed under 2.0-3.75V conditions to obtain the electrochemical performance of lithium iron phosphate, as shown in Table 3.

[0133] Table 1. Orthogonal proportions of ferric phosphate dihydrate, coefficient of variation of particle size, and other physicochemical properties.

[0134] Table 2. Coefficient of variation of iron phosphate particle size and physicochemical properties

[0135] Table 3 Compaction and electrochemical performance of cathode materials prepared in the examples and comparative examples

[0136] Combining Table 1 and Table 3 and Figures 1 to 4 As can be seen, the embodiments of this application, by adopting a two-stage co-precipitation preparation process and matching and limiting reasonable material ratios and process windows, have prepared iron phosphate dihydrate with an orthorhombic / monoclinic phase mixed phase ratio and particle size variation coefficient within a suitable range, and the corresponding electrochemical performance is also more excellent.

[0137] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A type of ferric phosphate dihydrate, characterized in that, The phases of the ferric phosphate dihydrate include a monoclinic phase and an orthorhombic phase, wherein the orthorhombic phase accounts for 50% to 85%; The particle size variation coefficient of the ferric phosphate dihydrate is <25%.

2. The ferric phosphate dihydrate according to claim 1, characterized in that, The particle size variation coefficient of the ferric phosphate dihydrate is ≤20%.

3. The ferric phosphate dihydrate according to claim 1 or 2, characterized in that, The ferric phosphate dihydrate satisfies one or more of the following conditions: (1) The ferric phosphate dihydrate comprises near-spherical particles, wherein the sphericity of the particles is 0.8 to 1.0; (2) The ferric phosphate dihydrate comprises spherical particles with an average size of 50 nm to 800 nm; (3) The specific surface area of ​​the ferric phosphate dihydrate is 3 m². 2 / g~30m 2 / g; (4) The tap density of the ferric phosphate dihydrate is 0.4 g / cm³. 3 ~2g / cm 3 ; (5) The iron-to-phosphorus molar ratio of the iron dihydrate ferric phosphate is 0.93~0.995; (6) The chemical formula of the iron phosphate dihydrate is Fe x M y PO4•2H2O; wherein, 0.95≤x≤1.00; 0≤y≤0.02; M includes one or more of Mn, V, Ti, Mg, Ca, Zn, Cu, Co, Ni, Al, Ga, In, La, Cr, and W.

4. A method for preparing ferric phosphate dihydrate, characterized in that, include: A soluble iron salt solution, an ammonium phosphate solution, and an oxidant were mixed and subjected to a first coprecipitation reaction, followed by aging to obtain an iron phosphate intermediate. The raw materials containing the ferric phosphate intermediate and the mixed acid solution are mixed to carry out a second coprecipitation reaction to obtain ferric phosphate dihydrate.

5. The method for preparing ferric phosphate dihydrate according to claim 4, characterized in that, The step of mixing the raw material containing the ferric phosphate intermediate with the mixed acid solution to carry out the second coprecipitation reaction is selected from one of the following methods: Method 1: Acidic medium and buffer medium are mixed to obtain a mixed acid solution; The mixed acid solution is heated to a preset slurrying temperature I, and the ferric phosphate intermediate is added to the heated mixed acid solution for slurrying treatment I to obtain a slurry mixture. The slurry mixture is heated to a preset aging temperature I for aging treatment to obtain ferric phosphate dihydrate. Method 2: A solution containing ferric phosphate intermediate was prepared by adding pure water to the ferric phosphate intermediate. Acidic medium and buffer medium are mixed to obtain a mixed acid solution; The solution containing the ferric phosphate intermediate is heated to a preset slurrying temperature II, and the mixed acid solution is added to the heated solution containing the ferric phosphate intermediate for slurrying treatment II to obtain a slurryed mixture; The slurry mixture is heated to a preset aging temperature II for aging treatment to obtain ferric phosphate dihydrate.

6. The method for preparing ferric phosphate dihydrate according to claim 5, characterized in that, The preparation method satisfies at least one of the following conditions: A. The preset pulping temperature I and preset pulping temperature II are each independently 70~85℃; optionally, the preset pulping temperature I and preset pulping temperature II are each independently 75~85℃; B. The pulping treatment I and pulping treatment II each have a time of 30~80 min independently; C. The preset aging temperature I and preset aging temperature II are each independently 90~100℃; D. The aging treatment I and aging treatment II each have an independent duration of 90-150 minutes; E. The acidic medium includes phosphoric acid and sulfuric acid.

7. The method for preparing ferric phosphate dihydrate according to claim 4 or 5, characterized in that, The preparation method satisfies at least one of the following conditions: (a) The soluble iron salt includes ferrous salts, which may be one or more of ferrous sulfate, ferrous chloride, ferrous oxalate, ferrous phosphate, and ferrous hydrogen phosphate; (b) The oxidant includes one or more of hydrogen peroxide, ozone, oxygen, and air; (c) The buffer medium includes one or more of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, ammonium sulfate, and ammonia water; (d) The raw material further includes solution M, wherein M is one or more of manganese, vanadium, titanium, magnesium, calcium, zinc, copper, cobalt, nickel, aluminum, gallium, indium, lanthanum, chromium, and tungsten; optionally, the molar ratio of M to iron in the ferric phosphate is 0 to 0.

04. (e) The molar ratio of the soluble iron salt solution, the ammonium phosphate solution, and the oxidant, calculated as iron atoms and phosphorus atoms, is Fe:P:oxidant (0.95~1.20):1:(0.6~0.7). (f) The molar ratio of Fe:N:P:S in the reaction system formed by the iron phosphate intermediate and the mixed acid solution, based on iron atoms, nitrogen atoms, phosphorus atoms, and sulfur atoms, is 1:(0.32-0.52):(0.7-1.3):(0.32-0.58); optionally, the molar ratio of Fe:N:P:S in the reaction system formed by the iron phosphate intermediate and the mixed acid solution is 1:(0.32-0.52):(0.7-1.1):(0.32-0.58); (g) The ammonium phosphate solution is selected from any one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate and ammonium phosphate, and is a mixed solution of these.

8. A type of iron phosphate, characterized in that, The ferric phosphate is obtained by heat treatment of ferric phosphate dihydrate prepared by any one of claims 1-4 or by any one of claims 5-7.

9. The ferric phosphate according to claim 8, wherein the ferric phosphate satisfies at least one of the following conditions: (i) The specific surface area of ​​the iron phosphate is 8 m². 2 / g~20m 2 / g; (ii) The iron-to-phosphorus molar ratio of the iron phosphate is 0.985 to 0.995; (iii) The particle size variation coefficient of the iron phosphate is less than 25%; (iv) The tap density of the iron phosphate is 0.6 g / cm³. 3 -0.8 g / cm 3 .

10. A battery positive electrode material, characterized in that, The raw materials for the battery cathode material include the iron phosphate described in claim 9.